PENERAPAN APLIKASI SAMSAT DIGITAL NASIONAL (SIGNAL) PADA WAJIB PAJAK KENDARAAN BERMOTOR RODA DUA DI SAMSAT KOTA BENGKULU - Kadek Maike; Achmad Aminudin; Is Susanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The advancement of information technology has encouraged the government to transform public services into digital-based systems. One such innovation is the National Digital Samsat Application (SIGNAL), which facilitates online Motor Vehicle Tax (PKB) payments. This study aims to analyze and describe the implementation of the SIGNAL application for two-wheeled motor vehicle taxpayers at Samsat Bengkulu City, using Riant Nugroho's policy implementation theory, which covers four aspects: socialization, implementation, supervision, and evaluation. This research uses a descriptive qualitative method with data collected through observation, interviews with five purposively selected informants, and documentation. The results show that the implementation of SIGNAL has not been fully optimal. Socialization has been carried out through direct approaches and social media (Instagram, TikTok) but has not reached all segments of society, particularly the elderly and those less familiar with digital platforms. The implementation stagedownloading the application, account registration, identity verification, and online tax paymenthas generally run according to procedure, though obstacles such as network disruptions and forgotten passwords remain. Supervision at the local level is limited to monitoring user numbers, while technical oversight of the system is centralized at the national level. Evaluation indicates a positive user response in terms of convenience, speed, and time efficiency, although the number of SIGNAL users is still not proportional to the total number of registered taxpayers in Bengkulu City.